How oxygen attacks [FeFe] hydrogenases from photosynthetic organisms. - Stripp, S; Goldet, G; Brandmayr, C; Sanganas, O; Vincent, K; Haumann, M; Armstrong, F; Happe, T (2009)
Green algae such as Chlamydomonas reinhardtii synthesize an [FeFe] hydrogenase that is highly active in hydrogen evolution. However, the extreme sensitivity of [FeFe] hydrogenases to oxygen presents a major challenge for exploiting these organisms to achieve sustainable photosynthetic hydrogen production. In this study, the mechanism of oxygen inactivation of the [FeFe] hydrogenase CrHydA1 from C. reinhardtii has been investigated. X-ray absorption spectroscopy shows that reaction with oxygen results in destruction of the [4Fe-4S] domain of the active site H-cluster while leaving the di-iron domain (2Fe(H)) essentially intact. By protein film electrochemistry we were able to determine the order of events leading up to this destruction. Carbon monoxide, a competitive inhibitor of CrHydA1 which binds to an Fe atom of the 2Fe(H) domain and is otherwise not known to attack FeS clusters in proteins, reacts nearly two orders of magnitude faster than oxygen and protects the enzyme against oxygen damage. These results therefore show that destruction of the [4Fe-4S] cluster is initiated by binding and reduction of oxygen at the di-iron domain-a key step that is blocked by carbon monoxide. The relatively slow attack by oxygen compared to carbon monoxide suggests that a very high level of discrimination can be achieved by subtle factors such as electronic effects (specific orbital overlap requirements) and steric constraints at the active site.